Implementation of the Heinrich Spatial Visualization Test in a Virtual Environment - Guzsvinecz, Tibor; Sik-Lanyi, Cecilia; Orban-Mihalyko, Eva; Perge, Erika (International Journal of Engineering and Management Sciences, 2021)
A virtual environment was developed for PC and Android to be used with a desktop display and the Gear VR, respectively. The goal with it is to measure and enhance the spatial skills of people, because the latter can be achieved by solving simple geometric problems. Originally, this virtual environment consisted only of three such tests, namely the Mental Rotation Test, Mental Cutting Test and Purdue Spatial Visualization Test. Measurements were done in the past with these tests, but now the Heinrich Spatial Visualization Test is also included in the virtual environment. In this paper, its implementation and future measurement plan are presented.